Application of The Fuzzy Promethee Method in Selecting Farmer Groups Verification for Candidates for Receiving Grants Regional Revenues And Expenditures Budget - Benny Rachman; Soewarto Hardhienata; Sufiatul Maryana (Ilmu Komputer, FMIPA, Universitas Pakuan, 2022)
The Bogor Regency Department of Fisheries and Livestock, in charge of the Breeding and Livestock Cultivation Section, has a work program to assist farmer groups, especially livestock, in acquiring aid funds from the government sourced from the Bogor Regency Regional Revenues and Expenditures Budget (APBD). As a result, the government allocates aid fundsfrom the Regional Revenues and Expenditures Budges (APBD) budget source to aid the community in managing livestock. Based on this, research will be conducted and methods used to determine which livestock farmer groups are eligible for government assistance will be implemented.A Decision Support System (DSS) will be used as a tool to recommend which farmer groups deserve assistance based on predetermined assessment criteria. By using the service, you will be able to provide a more accurate and objective evaluation. Because of its capacity to determine criteria values that contain uncertainty and select the best alternative based on these rankings and alternatives, the Fuzzy-PROMETHEE approach was chosen for handlingmulti criteria issues.